Circe’s struggle to fight against beauty standards in Madeline Miller’s Circe: A new criticism study - Pekerti, Mutiara Anugerah; Rosyidah, Usma Nur Dian; Datau, Rizal Oktovianto (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
Beauty standards are a cultural technique used to determine what is considered beautiful. Circe, Madeline Miller's story, exhibits a type of bias known as the beauty standard. Circe, the novel's main character and the daughter of Helios, the Sun God, is the subject of this study. Circe, the main character in this story, is treated differently, especially by her siblings, because she lacks the beautiful appearance and power of other Helios' children and ladies in her life. The goal of this study is to explain the cause of Circe's prejudice despite her upper-class status, the impact of beauty standards in Circe's life, and Circe's effort to combat beauty standards in society. This study was conducted using the New Criticism theory developed by W.K. Wimsatt and Monroe C. Beardsley. The writer adopts a qualitative descriptive method from the ground up. Circe encountered discrimination due to beauty standards, according to the findings of this study. Circe's appearance differed from that of most gods' progeny, so she did not meet these beauty standards. The writer then discovers the impact of these beauty standards on Circe's life, as well as the numerous efforts Circe makes to defy the beauty standards that surround her.